2020
DOI: 10.4187/respcare.07093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Prolonged Mechanical Ventilation Before and After Implementation of a Respiratory ICU

Abstract: BACKGROUND: Respiratory ICUs (RICUs) have recently been implemented in France to fill the gap between ICUs and respiratory wards for patients who will require prolonged mechanical ventilation (PMV). The aim of this study was to describe the outcomes of subjects with tracheostomy who were undergoing PMV before and after implementing a RICU in our hospital. METHODS: Two cohorts were studied and followed up for 1 year. Cohort 1 included 66 subjects from December 2010 to December 2012, before implementing the RICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Subsequently, we aimed at identifying potential underlying factors which contributed to an impaired OS in patients with an unfavorable body composition. As the time of mechanical ventilation on the ICU is a well-established prognostic factor for OS ( 10 ), we correlated the MMA with the duration of ventilation and observed a significant negative correlation between the HU and the total hours of mechanical ventilation on the ICU ( Fig. 3 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we aimed at identifying potential underlying factors which contributed to an impaired OS in patients with an unfavorable body composition. As the time of mechanical ventilation on the ICU is a well-established prognostic factor for OS ( 10 ), we correlated the MMA with the duration of ventilation and observed a significant negative correlation between the HU and the total hours of mechanical ventilation on the ICU ( Fig. 3 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Sobotka et al (22) found that more than half of the delayed discharges of children with prolonged mechanical ventilation were caused by a lack of professional or home care after discharge. Studies conducted in Europe, the US, and Taiwan have shown that the establishment of stepped up nursing units and weaning centers was an advantage to the weaning and nursing care of patients dependent on ventilators and the rational utilization of medical resources (6,8,(27)(28)(29)(30). A study in the United States showed that patients with home mechanical ventilation (HMV) had a lower rate of depression, pressure ulcers, and mortality patients in hospital long-term care (HLTC).…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall value of care in SWUs and LTACHs has been questioned due to the long care time and high mortality [10,85]. Herer et al showed that SWUs may improve weaning success and shorten hospital stays but do not affect 1-year mortality when compared to weaning in acute care hospitals [86]. Unfortunately, outcomes are especially poor for those who cannot be liberated from MV in SWU and are transferred to nursing homes or subacute care units.…”
Section: Location Of Ventilator Weaningmentioning
confidence: 99%